Clinical Decision Support for Alzheimer’s: Challenges in Generalizable Data-Driven Approach - Gao, Tianzheng; Madanian, Samaneh; Templeton, John; Merkin, Alexander (IOS Press, 2025)
This paper reviews the current research on Alzheimer's disease and the use of deep learning, particularly 3D-convolutional neural networks (3D-CNN), in analyzing brain images. It presents a predictive model based on MRI and clinical data from the ADNI dataset, showing that deep learning can improve diagnosis accuracy and sensitivity. We also discuss potential applications in biomarker discovery, disease progression prediction, and personalised treatment planning, highlighting the ability to identify sensitive features for early diagnosis.
Keywords: 3D-CNN; Deep Learning; Digital health; Neurodegenerative Diseases; 3D-CNN; Deep Learning; Digital health; Neurodegenerative Diseases; 46 Information and Computing Sciences; 4611 Machine Learning; Alzheimer's Disease including Alzheimer's Disease Related Dementias (AD/ADRD); Biomedical Imaging; Aging; Brain Disorders; Neurosciences; Bioengineering; Alzheimer's Disease; Dementia; Networking and Information Technology R&D (NITRD); Acquired Cognitive Impairment; Prevention; Neurodegenerative; Machine Learning and Artificial Intelligence; 4.1 Discovery and preclinical testing of markers and technologies; 4.2 Evaluation of markers and technologies; Neurological; 3 Good Health and Well Being; 0807 Library and Information Studies; 1117 Public Health and Health Services; Medical Informatics; 4203 Health services and systems; 4601 Applied computing; Alzheimer Disease; Brain; Decision Support Systems, Clinical; Deep Learning; Humans; Magnetic Resonance Imaging; Neural Networks, Computer; Alzheimer Disease; Humans; Decision Support Systems, Clinical; Magnetic Resonance Imaging; Deep Learning; Neural Networks, Computer; Brain; Brain; Humans; Alzheimer Disease; Magnetic Resonance Imaging; Decision Support Systems, Clinical; Deep Learning; Neural Networks, Computer; Alzheimer Disease; Humans; Decision Support Systems, Clinical; Magnetic Resonance Imaging; Deep Learning; Neural Networks, Computer; Brain